The Impact of Transatlantic Trade and Investment Partnership on the US and EU economies - Hoffmann, Petr (2016)
This master thesis is focused on the Transtlantic Trade and Investment Partnership and its possible impact on the EU and the US. The aim is to examine the economic and geopolitical implications that could come out of this deal. Closer look on this issue should bring a complex overview on the most discussed trade agreement in international relationship in the 21st century. Comparative approach will be used for detail analysis. Thesis deals with the comparison with current state of bilateral trade between EU and US. In more details TTIP negotiations are being described in this thesis as well its basic concept, advantages and disadvantages for both parties and impacts on Europe and US markets.